TNF Superfamily: A Growing Saga of Kidney Injury Modulators - Maria D. Sanchez-Niño; Alberto Benito-Martin; Sara Gonçalves; Ana B. Sanz; Alvaro C. Ucero; Maria C. Izquierdo; Adrian M. Ramos; Sergio Berzal; Rafael Selgas; Marta Ruiz-Ortega; Jesus Egido; Alberto Ortiz (Hindawi Limited, 2010)
Members of the TNF superfamily participate in kidney disease. Tumor necrosis factor (TNF) and Fas ligand regulate renal cell survival and inflammation, and therapeutic targeting improves the outcome of experimental renal injury. TNF-related apoptosis-inducing ligand (TRAIL and its potential decoy receptor osteoprotegerin are the two most upregulated death-related genes in human diabetic nephropathy. TRAIL activates NF-kappaB in tubular cells and promotes apoptosis in tubular cells and podocytes, especially in a high-glucose environment. By contrast, osteoprotegerin plays a protective role against TRAIL-induced apoptosis. Another family member, TNF-like weak inducer of apoptosis (TWEAK induces inflammation and tubular cell death or proliferation, depending on the microenvironment. While TNF only activates canonical NF-kappaB signaling, TWEAK promotes both canonical and noncanonical NF-kappaB activation in tubular cells, regulating different inflammatory responses. TWEAK promotes the secretion of MCP-1 and RANTES through NF-kappaB RelA-containing complexes and upregulates CCl21 and CCL19 expression through NF-kappaB inducing kinase (NIK-) dependent RelB/NF-kappaB2 complexes. In vivo TWEAK promotes postnephrectomy compensatory renal cell proliferation in a noninflammatory milieu. However, in the inflammatory milieu of acute kidney injury, TWEAK promotes tubular cell death and inflammation. Therapeutic targeting of TNF superfamily cytokines, including multipronged approaches targeting several cytokines should be further explored.